Measurement of important life events by support groups for the aged - Kuin, Y; Wimmers, M F (Tijdschrift voor gerontologie en geriatrie, 1988)
Research on important or stressful life events mainly refers to the causes and presence of somatic or psychiatric pathology. In most research checklists or questionnaires are used. Each item of the questionnaire corresponds with a life event. The subject has to indicate which life events had occurred in a restricted period before the onset of the illness, disorder, or behavioural changes. This method has some disadvantages, especially in use with the elderly. Other methods seem to be better for these subjects, e.g. the semi-structured interview. This method is based on the personal meaning and judgement of the subject. He or she can report important life events and the personal experience of feelings and cognitions. In our research with participants of support-groups of the elderly we used the interview-method. We asked the subjects which life events were important for them at that moment and in what way they experienced them (positively, negatively, or neutrally). This was asked before the start of the support-group and in two observations after the end of the group. The results show a change in the experience in a positive direction.